Serological and molecular evidence of enterovirus infection in patients with end-stage dilated cardiomyopathy. Issue 3 (September 1996) - Muir, P.; Nicholson, F.; Illavia, S. J.; McNeil, T. S.; Ajetunmobi, J. F.; Dunn, H.; Starkey, W. G.; Reetoo, K. N.; Cary, N. R.; Parameshwar, J.; Banatvala, J. E.
Abstract : OBJECTIVE: To study the relative diagnostic value of enterovirus-specific molecular biological and serological assays in patients with end-stage dilated cardiomyopathy, and to investigate the possible role of other cardiotropic viruses in dilated cardiomyopathy. DESIGN: Analysis of recipient myocardial tissue and serum from patients with dilated cardiomyopathy and controls undergoing cardiac transplantation for end-stage cardiac disease. SETTING: University virology department and transplantation unit. METHODS: Reverse transcriptase-polymerase chain reaction and nucleotide sequence analysis of myocardial RNA and DNA; enterovirus-specific in situ hybridization; enterovirus-specific immunoglobulin M detection. RESULTS: Enterovirus RNA was detected in myocardial tissue from only a small proportion of (five of 75) hearts. However, although enterovirus-specific immunoglobulin M responses were detected in 22 (28%) of 39 controls patients, a significantly higher prevalence was observed among patients with dilated cardiomyopathy (22 (56%) of 39 patients; P < 0.005). All enteroviruses detected in myocardium showed greatest nucleotide sequence homology with coxsackievirus type B3. Detection of enterovirus RNA in myocardium by the polymerase chain reaction and by in situ hybridisation gave comparable results. Other potentially cardiotropic virus genomes, including human cytomegalovirus, influenzaviruses, and coronaviruses were not detected in myocardium. CONCLUSION: This study found that enterovirus-specific immunoglobulin M responses provided the strongest evidence of enterovirus involvement in patients with end-stage dilated cardiomyopathy. However, the high background prevalence of these responses limits their diagnostic value. The finding that enteroviruses detected in myocardium were coxsackievirus type B3 accords with recent findings in patients with acute myocarditis, and indicates that this serotype is the major cardiotropic human enterovirus.